Numerical And Experimental Study On A Continuous Single Bubble Rising Behavior With And Without Heat Transfer Effect - Ismail, Nazmi Che (2014)
The behaviors of continuous single bubble rising phenomenon was studied using particle image velocimetry (piv) in a rectangular bubble column. A single bubble forms when a small amounts of air is released in the bubble column usually gas in a liquid rising from bottom to the upper surface. These processes are most important tools in industrial fluid mixing and oil production. As liquid viscosity changed, the velocity and trajectory of a bubbles change due to the formations of bubble wake structures. Plate heater with a presence of a single bubble rising in a fluid can enhance heat transfer by bubble motion pass through the heater surface. Heat transfer occurs when an object or physical systems exchange their thermal energy between them. The phenomenon happens when it has a different in temperatures from its surroundings or another object transfer it heated from one place to another by movement of fluids. The plate heater was immersed in the liquid with different locations and arrangements. These present study aim to investigate a single bubble interaction and motion using two different liquid viscosities with associated heat transfer over a vertical plate heater surface.